GMT and Longitude by Lunar Distance: Two Methods Compared From a Practitioner's Point of View. (2nd November 2019) - Romelczyk, Eric
Abstract : This article discusses the technique of observing lunar distance - that is, angular distance between the moon and another celestial body - to establish universal time and longitude, from a practitioner's point of view. The article presents a brief overview of the principles underlying the lunar distance observation and its use in celestial navigation. A discussion follows of two different methods for finding universal time by observing lunar distance, Dr. Wendel Brunner's calculator-based method and the specialised inspection tables created by Bruce Stark. The article compares the two methods against each other for ease of use and accuracy. The author concludes that either method will provide satisfactory results, but that the technique of observing lunar distance is unlikely to regain relevance in the modern-day practice of navigation and is primarily useful as a skill-building exercise in making sextant observations.